Pengaruh Disiplin Kerja, Gaya Kepemimpinan, Kompetensi Kerja Terhadap Produktivitas Kerja Pada Organisasi - Rizka Darlia (Journal Economic Excellence Ibnu Sina, 2023)
Work productivity is the result of work or job performance. However, work productivity actually has a broader meaning, not only in terms of the output but also in how the work processes occur. Work productivity is the outcome of tasks closely related to an organization's strategic goals, target satisfaction, and contribution to the organization. Employee work productivity can be influenced by several factors, including work discipline, leadership style, and job competency. The purpose of this research is to analyze the influence of various variables such as work discipline, leadership style, and job competency on work productivity within the 2021 batch of students at the Faculty of Economics, UNJ, in a partial manner. The data collection technique used in this research is the distribution of questionnaires with a Likert scale to 133 respondents. This study is of a quantitative descriptive nature. The data analysis technique used in this research employs structural equation modeling with a partial least squares (SEM-PLS) model calculated using the smart PLS software. The results of this research indicate that work discipline, leadership style, and job competency have a direct and significant positive influence on work productivity within the student organization of the Faculty of Economics, UNJ. Work discipline has a direct and significant influence on work productivity. Leadership style has a direct and significant influence on work productivity. Job competency has a direct and significant influence on work productivity.